Kemunduran Western European Union dalam Arsitektur Keamanan Eropa - Sindy Yulia Putri; Yosua Saut Marulitua Gultom (Jurnal Ilmiah Wahana Pendidikan, 2023)
This article aims to explain the Western European Union (WEU) in the dynamics of European regional security. We will start the article by identifying problems through the historical basis of the WEU’s formation. The WEU emerged after the second world war after the Modified Brussels Treaty (MBT), and was expected to appear as a pillar of European security architecture. The presence of the WEU in the European security constellation created a feud between the two camps, namely Atlantism and Europeanism. WEU based on the MBT has a mandate in the area of collective security and the economy. However, these tasks are then taken over by more established organizations such as NATO, or emerging ones such as the European Community (EC). This causes WEU to die as an institution. After the Rome declaration in 1984, WEU underwent a revitalization of its institution. But the spirit is back down. We believe that the decline in the spirit of revitalization was due to WEU's failure to deal with the Yugoslav crisis. At the end of the article, We conclude that Europe is not ready to create an independent security environment.